Translating concerns into action: a detailed qualitative evaluation of an interdisciplinary intervention on medical wards. Issue 4 (5th April 2017) - Pannick, Samuel; Archer, Stephanie; Johnston, Maximillian J; Beveridge, Iain; Long, Susannah Jane; Athanasiou, Thanos; Sevdalis, Nick
Abstract : Objectives: To understand how frontline reports of day-to-day care failings might be better translated into improvement. Design: Qualitative evaluation of an interdisciplinary team intervention capitalising on the frontline experience of care delivery. Prospective clinical team surveillance (PCTS) involved structured interdisciplinary briefings to capture challenges in care delivery, facilitated organisational escalation of the issues they identified, and feedback. Eighteen months of ethnography and two focus groups were conducted with staff taking part in a trial of PCTS. Results: PCTS fostered psychological safety—a confidence that the team would not embarrass or punish those who speak up. This was complemented by a hard edge of accountability, whereby team members would regulate their own behaviour in anticipation of future briefings. Frontline concerns were triaged to managers, or resolved autonomously by ward teams, reversing what had been well-established normalisations of deviance. Junior clinicians found a degree of catharsis in airing their concerns, and their teams became more proactive in addressing improvement opportunities. PCTS generated tangible organisational changes, and enabled managers to make a convincing case for investment. However, briefings were constrained by the need to preserve professional credibility, and staff found some comfort in avoiding accountability . At higher organisational levels, frontline concerns were subject to competition with other priorities, and their resolution was limited by the scale of the challenges they described. Conclusions: Prospective safety strategies relying on staff-volunteered data produce acceptable, negotiated accounts, subject to the many interdisciplinary tensions that characterise ward work. Nonetheless, these strategies give managers access to the realities of frontline cares, and support frontline staff to make incremental changes in their daily work. These are goals for learning healthcare organisations. Trial registration: ISRCTN 34806867.